Postperfusion lung syndrome and related sequelae - Yuan, Shi-Min (J Thorac Dis, 2016)
Postperfusion lung syndrome is a rare but sometimes lethal complication secondary to cardiopulmonary bypass. It often leads to multiorgan failure and mixed acid-base disturbances, thus making a refractory condition. A 69-year-old female, undergoing a successful cardiac lipoma resection under cardiopulmonary bypass, unfortunately developed postperfusion lung syndrome with associated multiorgan failure and triple acid-base disturbances (TABDs). Her condition deteriorated rapidly on postoperative day three and became moribund. This article reports a rare association following a surgical resection of cardiac lipoma, complicated with postperfusion lung syndrome and high-anion-gap and hyperchloride TABDs. It is recommended that proper positive end-expiratory pressure (PEEP) (5–10 cmH(2)O) with low tidal volume (6 mL/kg) be applied in order to minimize the compromise to cardiac function of cardiac surgical patients.